Assessing the impact of the special support measures for least developed countries: an analytical framework and some preliminary results - Patrick Guillaumont (Fondation pour les études et recherches sur le développement international (FERDI), 2011)
How far is it a benefit to be classified as a LDC? To address this issue several approaches are conceivable.A first approach would be to consider how the developing countries themselves perceive the benefits and costs of membership. [...]A second approach consists to review all the measures that have been taken by the international community specifically for the LDCs so that they can alone benefit. [....]A third approach is then to look for the real outcome of the measures designed for LDCs, in other words to assess their impact on the evolution of those countries.
Keywords: O19; O11; F35; F13; 330; PMA; Evaluation des mesures spéciales